2013
DOI: 10.1097/ico.0b013e31825ab9e2
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Image Evaluation System for Corneal In Vivo Confocal Microscopy

Abstract: The software rapidly and accurately analyzed the in vivo confocal micrographs of the healthy central corneas, yielding quantitative results to describe the nerves, dendritic immune cells, and wing cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 26 publications
(26 reference statements)
1
16
0
Order By: Relevance
“…Automated measurement of cellular structures for IVCM images, particularly for subbasal nerves, is an active area of the investigation, and recent studies have shown promising results for using such programs for future research. [40][41][42][43] In conclusion, our study demonstrates that the average values obtained from three representative standard IVCM images for the subbasal nerve and DC densities are comparable to those from the wide-field mapped composite images. Therefore, these standard images can be used in clinical studies to accurately measure cellular structures in the subbasal layer.…”
Section: Discussionsupporting
confidence: 49%
“…Automated measurement of cellular structures for IVCM images, particularly for subbasal nerves, is an active area of the investigation, and recent studies have shown promising results for using such programs for future research. [40][41][42][43] In conclusion, our study demonstrates that the average values obtained from three representative standard IVCM images for the subbasal nerve and DC densities are comparable to those from the wide-field mapped composite images. Therefore, these standard images can be used in clinical studies to accurately measure cellular structures in the subbasal layer.…”
Section: Discussionsupporting
confidence: 49%
“…Research groups have developed automated algorithms for analyzing the subbasal nerve plexus by IVCM, 96100 but, to date, there is no commercially available software for automated analysis of IVCM images. Scarpa et al 101 first devised a method for automatically tracing corneal nerves of confocal microscopy images, showing that automatic nerve length estimations were very well correlated to manual quantification.…”
Section: Assessment Of the Subbasal Corneal Nerve Plexusmentioning
confidence: 99%
“…Previous studies aimed at automatic fibre detection in CCM images include Scarpa et al [18] who described a method for tracing nerve fibres based on automatically initialised seed points, and Holmes et al [19]who identified fibres based on ridge points. Sindt et al [20] detected several types of objects visible in CCM images, including dendritic immune cells and wing cells in addition to nerve fibres. Dabbah et al [21] presented a method of fibre detection based on a multi-scale Gabor filter with responses trained using a neural network.…”
Section: Introductionmentioning
confidence: 99%